2015
DOI: 10.4067/s0718-221x2015005000041
|View full text |Cite
|
Sign up to set email alerts
|

Roughness and color evaluation of wood polymer composites filled by household waste of mate-tea

Abstract: This study presents the preparation of polypropylene composites filled with mixtures of household waste of mate-tea and wood particles to increase the economic value chain of mate-tea, especially in Latin America. Filler mixtures in proportions ranging from 0 to 60% depending on the type of particle were used. The polypropylene matrix was fixed at 40% and roughness surface and color evaluation were performed. The highest mean roughness (Ra) was observed for the composite with 30:30% proportion of filler mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The analysis of variance for the roughness parameter "Ra" obtained by the roughness analysis using a roughness drag is found in Table 3. The quality measurement of the machined surface by a roughness drag is suitable and important, as reported by Cademartori et al (2015). In this study, it was observed that no statistical differences were found between the analyzed treatments, that is, wood feeding rate and the rotation of the tool did not influence wood roughness.…”
Section: Quality Of the Machined Surfacementioning
confidence: 51%
“…The analysis of variance for the roughness parameter "Ra" obtained by the roughness analysis using a roughness drag is found in Table 3. The quality measurement of the machined surface by a roughness drag is suitable and important, as reported by Cademartori et al (2015). In this study, it was observed that no statistical differences were found between the analyzed treatments, that is, wood feeding rate and the rotation of the tool did not influence wood roughness.…”
Section: Quality Of the Machined Surfacementioning
confidence: 51%
“…The wood‐plastic composites, object of this research, were prepared according to the method already established for previous studies setting a target density of 1.15 g cm −3 for every formulation. The WPCs obtained had a flat and homogeneous distribution of the components as it can be observed in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…These composites are produced by extrusion, injection and molding at high temperature of the blend between classic polyolefin (e.g., PE, PP) and lignocellulosic fractions and therefore, they can be tailored for specific applications by modifying ratio and preparation conditions . Within the last decades, a number of researches were successfully led to exploit different lignocellulosic sources such as sugarcane, ramie, jute, linen, pineapple, sisal, coconut, cotton fibers, heart‐of‐peach palm sheath, orange pruning fibers for preparing bio‐based plastic composites, although the majority of the commercial applications are still based on wood sawdust and fibers .…”
Section: Introductionmentioning
confidence: 99%
“…Various lignocellulosic resources, like sugar cane fibers, ramie, jute, flax, pineapple, sisal, coconut fiber, castor seed cake, cotton, pupunha cover and wood residues, have been used to derive fibers and flours used in composite plastics (SATYANARAYANA et al, 2009;MAGALHÃES et al, 2013;MATTOS et al, 2014;CADEMARTORI et al, 2015c).…”
Section: Wood-plastic Compositesmentioning
confidence: 99%
“…These construction materials combine the mechanical resistance of wood with the formability and hydrophobicity of the polyolefin.The advantages of WPCs are that they are more environmentally sustainable than plastic alone, and they offer higher durability, lower maintenance and higher abrasion resistance than wood alone (EL-HAGGAR; KAMEL, 2011).Polymeric composites can be made using a matrix of high density polyethylene, HDPE (ZADOROZHNYY et al, 2016), polyethylene glycol, PEG(TSUBOI et al, 2016), polyethylene terephthalate, PET(MERIJS MERI et al, 2014), or polyvinyl chloride,PVC (YAZDANI et al, 2016). However, polypropylene, PP(MATTOS et al, 2014;CADEMARTORI et al, 2015c;CADEMARTORI et al, 2017) is used more widely for applications like automotive components, electrical devices, food packaging and household equipment(IZZATI ZULKIFLI et al, 2015). Its leading position in the WPC market is due to the combination of economicA.…”
mentioning
confidence: 99%